Line graphs of directed graphs I - Vaidyanathan Sivaraman; Daniel Slilaty (Transactions on Combinatorics)
We determine the forbidden induced subgraphs for the intersection of the classes of chordal bipartite graphs and line graphs of acyclic directed graphs. This is a first step towards finding the forbidden induced subgraphs for the class of line graphs of directed graphs.